Intraoperative implantation of 125I seeds improves prognosis in refractory stage IIIB cervical cancer: a case report and literature review - Jialin Wu; Junying Tang; Yi Luo; Wenbo Li; Yingwei Liu; Lin Xiao (BMC, 2024)
Abstract Background Concurrent chemoradiation is the standard treatment for advanced cervical cancer. However some patients still have a poor prognosis, and currently, there is no effective treatment for recurrence. In recent years, 125I seed implantation therapy has emerged as a treatment for advanced malignant tumors including surgically unresectable tumors, residual tumors after surgical resection, and metastatic tumors. However, the use of 125I seeds implantation in primary advanced cervical cancer has not been reported. In this study, we present a case of stage IIIB cervical cancer in a patient who had poor response to radiotherapy and chemotherapy. Subsequently, a radical hysterectomy was performed, and 125I radioactive seeds were successfully implanted during the surgery. This effectively controlled the lesions that were resistant to radiotherapy and had the potential to improve the prognosis. Case presentation A 56-year-old woman was diagnosed with stage IIIB (FIGO 2009) IIIC1r (FIGO 2018) squamous carcinoma of the cervix. After receiving 4 cycles of platinum-based chemotherapy and 30 rounds of radiotherapy, she underwent a radical hysterectomy. The localized cervical lesions were reduced, but there was no reduction in the size of the enlarged pelvic lymph nodes. Therefore, 125I seed implantation was performed under direct surgical vision for the right paracervical lesion and the enlarged pelvic lymph nodes on the right side. During the 18-month follow-up period, the enlarged lymph nodes subsided without any signs of recurrence or metastasis. Conclusion Intraoperative implantation of 125I seeds in lesions that are difficult to control with radiotherapy or in sites at high risk of recurrence is a feasible and effective treatment option for patients with advanced squamous cervical cancer, and it may contribute to improved survival.